2016
DOI: 10.1002/humu.23128
|View full text |Cite
|
Sign up to set email alerts
|

WRNMutation Update: Mutation Spectrum, Patient Registries, and Translational Prospects

Abstract: Werner syndrome (WS) is a rare autosomal recessive disorder characterized by a constellation of adult onset phenotypes consistent with an acceleration of intrinsic biological aging. It is caused by pathogenic variants in the WRN gene, which encodes a multifunctional nuclear protein with exonuclease and helicase activities. WRN protein is thought to be involved in optimization of various aspects of DNA metabolism, including DNA repair, recombination, replication, and transcription. In this update, we summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 95 publications
(130 reference statements)
3
98
0
Order By: Relevance
“…This patient carried a heterozygous Japanese founder mutation and a compound missense variant, c.1720G>A, p.Gly574Arg. The p.Gly574Arg was previously reported in a single German patient as a compound heterozygous mutation [Tadokoro et al, 2013;Yokote et al, 2017]. Although biochemical studies had already demonstrated the abrogation of enzymatic activities in a recombinant WRN protein with p.Gly574Arg [Tadokoro et al, 2013], the identification of the second p.Gly574Arg case further strengthens the notion of the pathogenicity of this variant and the loss of enzymatic activity as the cause of the WRN mutation.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…This patient carried a heterozygous Japanese founder mutation and a compound missense variant, c.1720G>A, p.Gly574Arg. The p.Gly574Arg was previously reported in a single German patient as a compound heterozygous mutation [Tadokoro et al, 2013;Yokote et al, 2017]. Although biochemical studies had already demonstrated the abrogation of enzymatic activities in a recombinant WRN protein with p.Gly574Arg [Tadokoro et al, 2013], the identification of the second p.Gly574Arg case further strengthens the notion of the pathogenicity of this variant and the loss of enzymatic activity as the cause of the WRN mutation.…”
Section: Resultsmentioning
confidence: 59%
“…Most of the pathogenic variants of the WRN gene were null mutations, either splicing, stop codon, or small indels [Yokote et al, 2017]. Amino acid substations within the exonuclease domain found in a German patient causes protein instability [Huang et al, 2006]; thus, they were also functionally null.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Virtually all pathogenic variants of WRN are null variants, with a few exceptions of amino acid substitutions that abolish its helicase activity and those that provoke protein instability, as reviewed by George M. Martin (International Registry of Werner Syndrome, University of Washington, USA) (Yokote et al, 2017). The most common initial symptom, which is often recognized retrospectively, is the lack of a growth spurt during one’s teens.…”
Section: Werner Syndromementioning
confidence: 99%